Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Loyalitas Karyawan Pada PT.PD. PAJA PINANG - Suci Etri Jayanti; Sri Winda Hardiyanti Damanik; Ayu Zurlaini; Prayogo Hardiantoani; Muhammad Akbar Prasetyo (Management And Business Progress, 2026)
This study aims to determine "The Influence of Organizational Culture and Work Environment on Employee Loyalty at PT. PD. PAJA PINANG". This type of research is quantitative. The sampling technique uses a Total Sampling technique of 79 samples which are all field employees of Afdiling 2 PT. PD PAJA PINANG. The data analysis method used is multiple linear regression using SPSS software. Based on the results of the analysis that the first hypothesis is accepted, meaning that the Organizational Culture variable (X1) has an effect on the Employee Loyalty variable (Y). The results of the second hypothesis analysis are rejected, meaning that the Work Environment variable (X2) does not have an effect on the Employee Loyalty variable (Y). And the results of the third hypothesis analysis are accepted, meaning that Organizational Culture (X1) and Work Environment (X2) simultaneously have an effect on the Employee Loyalty variable (Y)